Elements of Christian Thought : A Basic Course in Christianese - Rogers, Eugene F., Jr (Book collections on Project MUSE., 2021)
In the spring of 2020, as the coronavirus pandemic disrupted classrooms around the world, Eugene Rogers transcribed the lectures that make his Introduction to Christian Thought course justly famous. The result is an engaging introduction to the language--""Christianese""--That participants use to discuss God's activity in and for our world. From Anselm to Wyschogrod, Rogers introduces us to the most interesting speakers of Christianese, enabling us to take part in the living conversation